Association of ethylene oxide exposure with serum neurofilament light chain levels among American adults - Yang, Xiuwen; Feng, Huaili; You, Ting; Liu, Zhaoyi; Sun, Fanwei; Chen, Chengzhi; Qiu, Jingfu (Frontiers in Public Health, 2025)
ObjectiveTo explore the relationship between Ethylene oxide (EO) expousure and serum neurofilament light chain (NfL).MethodA data of 559 adults from the 2013–2014 National Health and Nutrition Examination Survey (NHANES) was analyzed, and the relationship between log-transformed EO hemoglobin adducts (HbEO) and serum NfL levels was assessed using multiple linear regression models and restricted cubic spline functions. Stratified analysis was conducted to explore the correlations within different subgroups. Mediation analysis was employed to investigate potential mediating factors.ResultsThe higher HbEO levels were consistently associated with elevated serum NfL concentrations among the study participants (β = 0.07, 95%CI: 0.00–0.14; p = 0.044), and serum NfL levels increased with rising HbEO levels (p for trend = 0.013). The restricted cubic spline results confirmed the linear relationship between serum NfL and HbEO. Subgroup analysis indicated a significant positive correlation, particularly among non-Hispanic white people, individuals aged 40–59, and heavy drinkers.ConclusionThese findings highlighted the neurotoxic potential of EO and underscored the importance of monitoring EO exposure to mitigate its adverse health effects.